TINJAUAN YURIDIS TINDAK PIDANA NARKOTIKA BAGI PEMAKAI DALAM PUTUSAN PENGADILAN NEGERI BANGKINANG NOMOR 511/PID-SUS/2020 PENGADILAN NEGERI BANGKINANG - Afrinaldi, Delfi; Prayudi Saputra, Rian; Firmanto, Fakhry (Jurnal Pahlawan, 2022)
Narcotics are drugs or substances that are useful in the fields of medicine, health services and scientific development, but on the other hand can cause very detrimental dependency if used without strict and careful control, supervision. The formulation of the problem in this study is How is the application of the Narcotics Crime law for users in Decision Number 511 / Pid-Sus / 2020 / PN Bkn and How are the judge's legal considerations in passing decisions on Narcotics Crime Defendants in Decision Number 511 / Pid-Sus / 2020 / PN Bkn. The method used is a normative legal approach, This study uses a normative legal method, with a qualitative approach. The nature of the research The nature of this research is descriptive research. The aim is to describe precisely, accurately, and systematically the decision of the Bangkinang District Court Number 511 / Pid-Sus / 2020 Bangkinang District Court. The result obtained is a trial process ends with the passing of a final decision (verdict) which includes the imposition of criminal sanctions (punishment) on the guilty defendant, and in the verdict the judge states his opinion about what has been considered and what is the verdict. Before reaching that stage, there are stages that must be carried out beforehand, namely the stage of proof in imposing a criminal sentence on the defendant. Keywords: Crime, Narcotics, Users.